Disinfection methods of dental unit waterlines contamination: a systematic review. Issue 6 (6th June 2022) - Wu, Mengting; Shi, Zhiwei; Yu, Xuefen; Xu, Yuedan; Jin, Xinyang; Zhang, Ling; Fu, Baiping
Abstract : Background. Severe contamination of dental unit waterlines was found in healthcare settings. The benefits of decontamination methods are controversial. The aim of this review was to systematically evaluate disinfection methods in contamination control of dental unit waterlines. Methods. The terms 'dental unit waterline(s) or DUWL(s) or dental unit water line(s)' were searched through PubMed, Cochrane Library, Embase, Web of Science and Scopusup to 31 May 2021. The DUWLs' output water was incubated on R2A agar at 20–28 °C for 5–7 days to evaluate heterotrophic mesophilic bacteria. The risk of bias was evaluated by a modified Newcastle-Ottawa quality assessment scale. Results. Eighteen papers from the literature were included. One study indicated that water supply played a crucial role in disinfecting DUWLs. Three studies indicated that flushing decreased bacteria counts but did not meet the American CDC standard (500 c.f.u. ml −1 ). All chlorine- and peroxide-containing disinfectants except sodium hypochlorite in one of 15 studies as well as three mouthrinses and citrus botanical extract achieved the standard (≤500 c.f.u. ml −1 ). The included studies were of low (1/18), moderate (6/18) and high (11/18) quality. Conclusion. Independent water reservoirs are recommended for disinfecting DUWLs using distilled water. Flushing DUWLs should be combined with disinfections. Nearly all the chlorine-, chlorhexidine- and peroxide-containing disinfectants, mouthrinses and citrus botanical extract meet the standard for disinfecting DUWLs. Alkaline peroxide would lead to tube blockage in the DUWLs. Regularly changing disinfectants can reduce the risk of occurrence of disinfectant-resistant strains of microbes.